Nine Months of Hybrid Intradialytic Exercise Training Improves Ejection Fraction and Cardiac Autonomic Nervous System Activity - Christoforos D. Giannaki; Stefania S. Grigoriou; Keith George; Christina Karatzaferi; Paris Zigoulis; Eleftherios Lavdas; Dimitrios Chaniotis; Ioannis Stefanidis; Giorgos K. Sakkas (MDPI AG, 2023)
Cardiovascular disease is the most common cause of death in hemodialysis (HD) patients. Intradialytic aerobic exercise training has a beneficial effect on cardiovascular system function and reduces mortality in HD patients. However, the impact of other forms of exercise on the cardiovascular system, such as hybrid exercise, is not clear. Briefly, hybrid exercise combines aerobic and strength training in the same session. The present study examined whether hybrid intradialytic exercise has long-term benefits on left ventricular function and structure and the autonomous nervous system in HD patients. In this single-group design, efficacy-based intervention, twelve stable HD patients (10M/2F, 56 ± 19 years) participated in a nine-month-long hybrid intradialytic training program. Both echocardiographic assessments of left ventricular function and structure and heart rate variability (HRV) were assessed pre, during and after the end of the HD session at baseline and after the nine-month intervention. Ejection Fraction (EF), both assessed before and at the end of the HD session, appeared to be significantly improved after the intervention period compared to the baseline values (48.7 ± 11.1 vs. 58.8 ± 6.5, p = 0.046 and 50.0 ± 13.4 vs. 56.1 ± 3.4, p = 0.054 respectively). Regarding HRV assessment, hybrid exercise training increased LF and decreased HF (p < 0.05). Both conventional Doppler and tissue Doppler imaging indices of diastolic function did not change after the intervention period (p > 0.05). In conclusion, long-term intradialytic hybrid exercise training was an effective non-pharmacological approach to improving EF and the cardiac autonomous nervous system in HD patients. Such exercise training programs could be incorporated into HD units to improve the patients' cardiovascular health.